A historical narrative of the development of midwifery education in Indonesia. Issue 1 (February 2023) - Adnani, Qorinah Estiningtyas Sakilah; Gilkison, Andrea; McAra-Couper, Judith
Abstract: Aim: To describe the history of midwifery education, present the current education programmes and explore the ways that have been undertaken to advance the midwifery profession in Indonesia. Methods: Historical and contemporary government documents were reviewed. Findings: The history of midwifery education in Indonesia shows a complex picture during and since colonisation with government, education institutes and association proposing different ways in which midwives were to be educated. Advocacy from the midwifery profession in Indonesia meant increasingly it is midwives who are determining how midwifery education is provided. Recent initiatives have resulted in a diploma, advanced diploma, bachelor's degree, and a master's degree in midwifery. The work of the midwifery profession advocating for midwifery education culminated in the Midwifery Act 2019. These changes in this Act will ensure that midwifery education meets the needs of women and their families but also lead to competent midwives who have the knowledge and skills to provide midwifery services at all levels of health provision. The history of midwifery in Indonesia illustrates the importance of the ICM pillars of association, regulation, and education. Conclusion: The history of midwifery education in Indonesia shows that for too long midwifery education was decided, determined and even regulated by authorities and disciplines other than midwifery. However, when the midwifery association and regulation inform and regulate midwifery education then there is an opportunity to provide care that will make a difference in outcomes for women and their families. The historical analysis of the story of Indonesia midwifery gives insight into what is required for quality education.